The spoken (he)art of strategy: A metaphor analysis of the strategy discourse of 10 South African business executives - J. Foster-Pedley; D. Bond; R. Brown (South African Journal of Business Management, 2005)
This paper investigates the importance of metaphor in strategy in several ways. Firstly it considers the problematic nature of `strategy' itself. Next, it outlines some views on how metaphor is used in strategy discourse, with particular emphasis on innovation, emergent processes and sense-making. It is then proposed that not only is metaphor useful in describing or making sense of strategy, but it is also central to `doing' strategy - that strategy is, in important ways, metaphoric.This paper explores the proposition that research methods based on metaphor analysis can provide fundamental and useful insights into how business strategy is performed and understood. It also raises questions about the way strategy is taught. A description follows providing the results of research carried out on ten senior business executives in South Africa. A number of conclusions are derived from this research:(i) metaphor, which is useful in communicating ideas and meanings, appears to emerge as required to emphasize, construct new meaning and persuade rather than as a tool to support any particular dominant interest(ii) metaphor opens up paradoxical space(iii) metaphor is fundamental in articulating strategy(iv) speakers were generally not aware of their use of metaphor, in spite of a frequent richness of metaphor use(v) when the speakers were made aware of their use of metaphor, they were less able to engage in further discussion using metaphor and(vi) when ceasing to use metaphor, they seemed less able to engage in discussion and thought about strategy.Finally, some questions are raised from a more `critical' perspective. The critical analysis in our paper tests a synthesis of the analytical frameworks of Lakoff and Johnson (1980) and Fairclough (1989;1992b) to see what can be 'surfaced' through this type of metaphor analysis, and consider what implications there may be for management education.Ultimately, the heart of strategy may lie in the art of sense-making and creativity via discourse and conversation. Part of this spoken art lives in and by metaphor, which lightens and eases the paths to new understandings, new directions and to new configurations of individuals, firms and markets.
Keywords: 650